Connexins in respiratory and gastrointestinal mucosal immunity. Issue 8 (12th March 2014) - Bou Saab, Joanna; Losa, Davide; Chanson, Marc; Ruez, Richard
Abstract : The mucosal lining forms the physical and chemical barrier that protects against pathogens and hostile particles and harbors its own population of bacteria, fungi and archea, known as the microbiota. The immune system controls tolerance of this population of microorganisms that have proven to be beneficial for its host. Keeping its physical integrity and a correct balance with the microbiota, the mucosa preserves its homeostasis and its protective function and maintains host's health. However, in some conditions, pathogens may succeed in breaching mucosal homeostasis and successfully infecting the host. In this review we will discuss the role the mucosa plays in the defense against bacterial pathogens by considering the gap junction protein connexins. We will detail their implication in mucosal homeostasis and upon infection with bacteria in the respiratory and the gastrointestinal tracts.